(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The rights of the poor in India are as fundamental as those of the rich. People are the real wealth of nation, the basic purpose of development is to enlarge human freedom. The crucial instrumental freedoms are economic opportunities, political freedoms, transparency guarantees and protective security because the democracy and development are linked in fundamental ways.According to the view of Amartya Sen, their development is the quality of life in terms of capability expansion which explains development as freedom and capability to function. That is what we do with what we have. Capabilities include endowment, individual capacity and social opportunity.